The Effectiveness of the Scientifict Approach to Children’s Abilities at the Padang Bahari Kindergarten - Putri Mardiyah Ritonga; Zulminiati Zulminiati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
The purpose of this study is to determine the effectiveness of the scientific approach to children’s scientific abilities at TK Bahari Padang. Learning activities carried out are activities to make traditional herbal medicine using a scientific approach, so as to able to develop children’s scientific availabilities in this study using quantitative research types in the form of quasy experiments, with a research population of all 48 children’s of Bahari Padang kindergarten. Class B4 is a sample as an experimental class and B1 as a control class, each class consists of 12 children with purposive sampling research techniques and data collection tools used statemen sheets and then the data, which was previously tested for normality and homogeneity, as well as the N-Gain score. And the result of the study showed the average value of the control class was 3,33333 and the experimental class was 8, 3333 and the results of the influence or effect size test 3,41927. Then based on the analysis of the result of the hypothesis test and the effect size test, the scientific approach was effective on the ability children’s science in Padang Bahari kindergarten. Keywords: Scientific Approach, Scientific Ability